Effect of Bleaching Agents on the Bond Strength of Orthodontic Brackets - Perthish Sharma; Mayur Kumar Soni; Anurag Sahu; Y Sarita; Mona Janak Shah; Rahul Ganavadiya; Mahesh Ghadage; Dipooja Patil (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: One common technique for tooth whitening is the use of bleaching chemicals, which is often done either before or during orthodontic treatment. The impact of these chemicals on the binding strength of orthodontic brackets is a matter of concern, however. Materials and Methods: Sixty recently removed human premolars were used in this in vitro investigation. They were split into three groups at random: Group A—control, no bleaching—Group B—bleaching with 10% carbamide peroxide, and Group C—bleaching with 35% hydrogen peroxide. Orthodontic brackets were glued using a light-cure adhesive after bleaching. A universal testing machine was used to determine the shear bond strength, and failure patterns were evaluated by recording the adhesive remnant index (ARI). ANOVA and post hoc Tukey tests were used to examine the data, with a significance threshold of P < 0.05. Results: Groups A, B, and C have mean shear bond strengths of 18.5 ± 2.1 MPa, 14.3 ± 2.4 MPa, and 11.7 ± 1.9 MPa, respectively. All of the groups showed significant differences (P < 0.05). Group C had the weakest link, suggesting that 35% hydrogen peroxide had a more detrimental impact than 10% carbamide peroxide. Group A had more adhesive remains on the enamel surface than Groups B and C, according to ARI ratings. Conclusion: The binding strength of orthodontic brackets is considerably decreased by bleaching chemicals, with larger losses occurring at increasing doses. After bleaching, clinicians should think about postponing bracket bonding treatments or using techniques to strengthen the enamel bond.